Concurrent hiatal hernia repair and bariatric surgery: outcomes after sleeve gastrectomy and Roux-en-Y gastric bypass - Lewis, Kristina H.; Callaway, Katherine; Argetsinger, Stephanie; Wallace, Jamie; Arterburn, David E.; Zhang, Fang; Fernandez, Adolfo; Ross-Degnan, Dennis; Dimick, Justin B.; Wharam, J. Frank (Surgery for obesity and related diseases, 2021)
Hiatal hernias are often repaired concurrently with bariatric surgery to reduce risk of gastroesophageal reflux disease–related complications. To examine the association between concurrent hiatal hernia repair (HHR) and bariatric outcomes. A 2010–2017 U.S. commercial insurance claims data set. We conducted a retrospective cohort study. We identified adults who underwent sleeve gastrectomy (SG) or Roux-en-Y gastric bypass (RYGB) alone or had bariatric surgery concurrently with HHR. We matched patients with and without HHR and followed patients up to 3 years for incident abdominal operative interventions, bariatric revisions/conversions, and endoscopy. Time to first event for each outcome was compared using multivariable Cox proportional hazards modeling. We matched 1546 SG patients with HHR to 3170 SG patients without HHR, and we matched 457 RYGB patients with HHR to 1156 RYGB patients without HHR. A total of 73% had a full year of postoperative enrollment. Patients who underwent concurrent SG and HHR were more likely to have additional abdominal operations (adjusted hazard ratio [aHR], 2.1; 95% CI, 1.5–3.1) and endoscopies (aHR, 1.5; 95% CI, 1.2–1.8) but not bariatric revisions/conversions (aHR, 1.7; 95% CI, .6–4.6) by 1 year after surgery, a pattern maintained at 3 years of follow-up. Among RYGB patients, concurrent HHR was associated only with an increased risk of endoscopy (aHR, 1.4; 95% CI, 1.1–1.8)) at 1 year of follow-up, persisting at 3 years. Concurrent SG/HHR was associated with increased risk of some subsequent operative and nonoperative interventions, a pattern that was not consistently observed for RYGB. Additional studies could examine whether changes to concurrent HHR technique could reduce risk. •Concurrent hiatal hernia repair with SG is associated with higher risk of reoperation•Concurrent hiatal hernia repair with RYGB is associated with higher risk of endoscopy